Circular RNA TAF4B Promotes Bladder Cancer Progression by Sponging miR-1298-5p and Regulating TGFA Expression - Zhang, Xiaoting; Li, Xiaofeng; Fu, Xian; Yu, Mengli; Qin, Guicheng; Chen, Guihong; Huang, Chenchen (Frontiers in Oncology, 2021)
Background Bladder cancer (Bca) is the most common malignant tumor of the urinary system. Circular RNAs (circRNAs) have been recognized as key regulators in tumorigenesis. However, the molecular mechanisms underlying circRNAs involved in the progression of BCa remain largely unknown. Methods We detected the expression level of circular RNA TAF4B (circTAF4B) by qRT-PCR assay. Cell proliferation was evaluated by CCK-8 and colony formation assays. Wound healing and Transwell assays were performed to measure cell migration and invasion capability. Moreover, we performed qRT-PCR and western blotting assays to determine the expression levels of epithelial-mesenchymal transition (EMT) markers. A nuclear/cytoplasmic fractionation assay was used to measure the subcellular location of circTAF4B. RNA pull-down and dual-luciferase reporter assays were used to detect the target microRNA of circTAF4B. A mouse xenograft model was produced to analyze the effect of circTAF4B on the tumorigenesis of BCa. Results In this study, we identified a novel circular RNA, circTAF4B, that is significantly upregulated in BCa and correlated with poor prognosis. Downregulated circTAF4B abolished the growth, metastasis and EMT process in BCa cells. Mechanistically, we found that circTAF4B facilitated the expression of transforming growth factor A (TGFA) by sponging miR-1298-5p. Finally, circTAF4B enhanced the proliferation and EMT process of BCa cells in vivo. Conclusion In summary, our study demonstrated that circTAF4B played a carcinogenic role in the growth, metastasis, and EMT process of BCa by regulating the miR-1298-5p/TGFA axis. Thus, circTAF4B may become a diagnostic and therapeutic target for BCa.